(untitled) (Bangladesh Journal of Agricultural Research, 2013)
The field experiment was conducted at the Eastern Region of Sri Lanka to evaluate the effects of cattle manure with EM soil application on the yield and yield components of groundnut (Arachis hypogaea L.) cv Indi. It consisted of 10 treatments replicated four times in a randomized complete block design. Treatments were five levels (0, 5, 10, 15 and 20 t/ha) of cattle manure (CM) with and without EM soil application. Air dry cattle manure was incorporated into soil two weeks before sowing and EM solution was sprayed to soil at two week intervals from flowering to maturity of the crop. All other agronomic practices were followed according to the recommendation. The results showed that the increase of cattle manure (up to 15 t/ha) combined with EM increased the number of pods, weight of pods and kernels per plant, 100-kernel weight, shelling % and total yield. Higher kernel yield (3.42 t/ha) was obtained from 15 t/ha CM + EM application. The kernel yield in the control treatment (chemical fertilizer only) was 2.78 t/ha, which was comparable to 2.81 t/ha of kernel with 15 t/ha CM application alone. This study revealed that cattle manure at the rate of 15 t/ha coupled with EM would give better yield of groundnut and it can replace chemical fertilizer use. Bangladesh J. Agril. Res. 38(1): 1-9, March 2013 DOI: http://dx.doi.org/10.3329/bjar.v38i1.15184